ZEOLITES IN MEDICINE AND TURKEY ZEOLITES - Bilgin, Öykü; Koç, Ercüment (STEF92 TECHNOLOGY, 2013)
Zeolites are a mineral group which as a result of variation of volcanic ashes in the aquatic environment millions of years ago, consisting of alkaline and alkaline earths' hydrated natural silicates. The most important feature of zeolite minerals are "molecular sieve" that liquid and gas molecules with alkaline earth ions which can enter the spaces easily and can change place. In Turkey zeolites which have an important position with very extensive reserves; are available in the Manisa(Gordes), Ankara(Polatli-Nallihan-Beypazari), Kutahya(Saphane), Izmir(Urla), Balikesir(Bigadic). In these regions; zeolite minerals are named clinoptilolite, heulandite, analcime, chabazite, erionite. Zeolites have extensive utilization areas. Zeolites contribute to a cleaner, safer environment in a great number of ways. In fact nearly every application of zeolites has been driven by environmental concerns, or plays a significant role in reducing toxic waste and energy consumption. Zeolites are used in agriculture due to the properties such as ion change, water and gas holding; in fishery; in water, gas and radioactive waste cleaning; in drying; in sun and gas storage; in odor control; as a structural element; in making good quality paper and many areas. This study examines Turkey zeolite formation and use of zeolites in medicine.
Keywords: Turkey zeolite; Usage areas; Zeolite; Medicine